Long‐range transport of NH3, CO, HCN, and C2H6 from the 2014 Canadian Wildfires - E. Lutsch; E. Dammers; S. Conway; K. Strong (Geophysical Research Letters)
Abstract We report the first long‐term measurements of ammonia (NH3) in the high Arctic. Enhancements of the total columns of NH3, carbon monoxide (CO), hydrogen cyanide (HCN), and ethane (C2H6) were detected in July and August 2014 at Eureka, Nunavut, and Toronto, Ontario. Enhancements were attributed to fires in the Northwest Territories using the FLEXPART Lagrangian dispersion model and the Moderate Resolution Imaging Spectroradiometer Fire Hot Spot data set. Emission estimates are reported as average emission factors for HCN (0.62 ± 0.34 g kg−1), C2H6 (1.50 ± 0.75 g kg−1), and NH3 (1.40 ± 0.72 g kg−1). Observations of NH3 at both sites demonstrate long‐range transport of NH3, with an estimated NH3 lifetime of 48 h. We also conclude that boreal fires may be an important source of NH3 in the summertime Arctic.